2002
DOI: 10.1046/j.1365-2141.2002.03589.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal gammopathy in Iceland: a population‐based registry and follow‐up

Abstract: Summary. The term monoclonal gammopathy (MG) signifies the benign or malignant clonal growth of B lymphocytes. In the present study, monoclonal gammopathy of unknown significance (MGUS) was defined as those patients with no identified haematological malignancy. A database was constructed of all 713 MG patients in Iceland between 1976 and 1997 and compared with the Icelandic Cancer Registry. The age-standardized incidence per 100 000 of MG was 10AE3 for males and 8AE6 for females, calculated for the whole perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 22 publications
4
16
0
1
Order By: Relevance
“…As for the transformation from MGUS to MM, a quarter of MGUS patients developed lymphoid malignancies, 66% of which were MM, within 20-35 years of onset (Gregersen et al, 2001;Kyle et al, 2002). In our study, no lymphoid neoplasms other than MM developed among MGUS patients, although other studies have reported a variety of lymphoid malignancies besides MM, including IgM lymphoma, macroglobulinaemia and chronic lymphocytic leukaemia (Kanoh et al, 1990;Blade et al, 1992;van de Poel et al, 1995;Lolin et al, 1996;Ong et al, 1997;Vuckovic et al, 1997;Colls, 1999;Gregersen et al, 2001;Kyle et al, 2002;Ogmundsdottir et al, 2002). The transformation rate in the present study, 21% at 16 years, is quite similar to that of others, for example 12% at 10 years and 25% at 20 years (Kyle et al, 2002), 8AE5% at 5 years and 19AE2% at 10 years (Blade et al, 1992), and 11% at 14 years (van de Poel et al, 1995).…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…As for the transformation from MGUS to MM, a quarter of MGUS patients developed lymphoid malignancies, 66% of which were MM, within 20-35 years of onset (Gregersen et al, 2001;Kyle et al, 2002). In our study, no lymphoid neoplasms other than MM developed among MGUS patients, although other studies have reported a variety of lymphoid malignancies besides MM, including IgM lymphoma, macroglobulinaemia and chronic lymphocytic leukaemia (Kanoh et al, 1990;Blade et al, 1992;van de Poel et al, 1995;Lolin et al, 1996;Ong et al, 1997;Vuckovic et al, 1997;Colls, 1999;Gregersen et al, 2001;Kyle et al, 2002;Ogmundsdottir et al, 2002). The transformation rate in the present study, 21% at 16 years, is quite similar to that of others, for example 12% at 10 years and 25% at 20 years (Kyle et al, 2002), 8AE5% at 5 years and 19AE2% at 10 years (Blade et al, 1992), and 11% at 14 years (van de Poel et al, 1995).…”
Section: Discussionsupporting
confidence: 41%
“…The prevalence of MGUS in the general population is 2AE0% in those over 50 years old and 3AE0% in those over 70 years of age (Kyle et al, 2002), but there are a few population-based studies on the incidence of MGUS (Ong et al, 1997;Ogmundsdottir et al, 2002). Atomic bomb (A-bomb) survivors, on whom epidemiological studies have been conducted for many years to assess the effects of radiation on humans, provide a unique population for such a study.…”
mentioning
confidence: 99%
“…The highest incidence rate was reported in a study of approximately 7000 atomic bomb survivors in Japan. Significantly lower incidence rates were found in retrospective registrybased studies by Ogmundsdóttir et al 25 and Ong et al 26 aGe Six studies each reported prevalence data across several age groups (Figure 1). The largest of these studies by Kyle et al 13 found the prevalence of MGUS to be 4-fold higher in those older than 80 years (6.6%) compared with those aged 50 to 59 years (1.7%) in a sample of approximately 22,000 people.…”
Section: Prevalence Of Mgusmentioning
confidence: 83%
“…Over time, electrophoretic techniques have improved, and tests such as protein immunofixation and the serum free light chain assay have greatly increased the sensitivity of detecting M proteins in the serum. 25 The differences in sensitivities of laboratory tests used to identify M protein may influence studies' estimates of the prevalence of MGUS. 13 Furthermore, the second diagnostic criterion of MGUS requires the proportion of clonal plasma cells to be less than 10% in bone marrow.…”
Section: Sexmentioning
confidence: 99%
“…8,10,335,[339][340][341][342][343][344][345][346][347] In the original Mayo Clinic series of 241 patients with MGUS, 39% developed multiple myeloma within 25 years of follow-up. 335 In a larger cohort, Kyle et al 8 reported a highly increased risk of multiple myeloma (RR 5 25.0, 95% CI: 20.0-32.0) among 1,384 residents of southeastern Minnesota in whom MGUS was diagnosed in 1960 through 1994.…”
mentioning
confidence: 99%